2019
DOI: 10.1177/1060028019828423
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rescue Thrombolysis in Cardiac Arrest Secondary to Suspected or Confirmed Pulmonary Embolism

Abstract: Background: Pulmonary embolism (PE) is the associated cause of unexplained cardiac arrest in 5% to 13% of patients. Although thrombolytic agents have been studied, patient outcomes during cardiac arrest are lacking. Objective: The purpose of this study was to describe outcomes of patients who received thrombolytic therapy during cardiac arrest for suspected or confirmed PE. Methods: This retrospective review included adults who received alteplase or tenecteplase during cardiac arrest for suspected or confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
4
1
2
Order By: Relevance
“…Our cohort had similar short times to ROSC It is also possible that non-documented contraindications were present in patients with suspected PE not receiving thrombolysis. Nevertheless, our results are consistent with the findings of Summers et al, 8 who reported no events of major bleeding in 22 patients with PE-related IHCA who had been administered thrombolysis. It should further be noted that cases of minor bleeding in our study were seemingly unrelated to CPR, and not more common in patients where thrombolysis was initiated during CPR than in those where it was initiated before or after.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our cohort had similar short times to ROSC It is also possible that non-documented contraindications were present in patients with suspected PE not receiving thrombolysis. Nevertheless, our results are consistent with the findings of Summers et al, 8 who reported no events of major bleeding in 22 patients with PE-related IHCA who had been administered thrombolysis. It should further be noted that cases of minor bleeding in our study were seemingly unrelated to CPR, and not more common in patients where thrombolysis was initiated during CPR than in those where it was initiated before or after.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies have assessed treatment for PE given intra-arrest, but some observational studies on out-of-hospital cardiac arrest (OHCA) and PE have shown no difference 7. , 8. or increased survival among those receiving thrombolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Der ERC empfiehlt den routinemäßigen Einsatz von Thrombolytika bei Kreislaufstillstand nicht, es sei denn bei vermuteter oder bestätigter LE. Wenn Thrombolytika verabreicht wurden, sollen die Wiederbelebungsmaßnahmen mindestens 60 bis 90 min lang vor Abbruch fortgeführt werden [ 330 332 ].…”
Section: Evidenz Für Die Leitlinienunclassified
“…Es gibt keine ausreichenden Nachweise, um eine Empfehlung bezüglich eines optimalen Medikaments oder einer Dosierungsstrategie zur Thrombolyse während der Wiederbelebung geben zu können [ 2 ]. Wenn Thrombolytika verabreicht wurden, sollen Sie erwägen, die Wiederbelebungsversuche für mindestens 60–90 min fortzusetzen, bevor Sie die Wiederbelebungsversuche einstellen [ 230 232 ].…”
Section: Evidenz Die In Die Leitlinien Einfließtunclassified